Some principles of pig nutrition in the tropics - Pezo, Danilo A. (International Potato Center, 2001)
Small-scale rural farmers cannot complete with the large-scale, peri-urban, and vertically integrated systems using the same type of feed resources (i.e. imported grain cereals and protein sources), animal genotypes and facilities. In order to succeed, these farmers need to develop alternative pig production systems, mainly based on the use of locally available feed resources, preferably produced in the same farm, and avoiding as much as possible. however, in order to make an efficient use of those resources, it is necessary to understand the principles that govern swine nutrition, as well as the impact of using feed resources with generally low dry matter content, and rich in sugars, lipids and/or fiber. This paper illustrates the digestive tract of pig and sheep and examines the energy requirements and supplementation of sweet potato-based diets.